Interpersonal Communication in Deaf Families - Leony Setia Rahmita; Nur Maghfirah Aesthetika (Indonesian Journal of Cultural and Community Development, 2022)
The purpose of this study was to find out how interpersonal communication in families with hearing impairments is. Data analysis was carried out by analysis according to Miles and Huberman which consisted of data reduction, data presentation and verification withdrawal. The result of this research is that the communication that exists between the speakers is a complex interpersonal communication. Where in practice, parents with hearing impairment can still communicate with their normal-hearing children. Both verbally and non-verbally, directly or through intermediaries. In addition, the results of the study indicate that parents with hearing impairment as well as children and family members with normal hearing have applied aspects of interpersonal communication. The research conducted also shows that various obstacles experienced by both parents with hearing impairment and family members with normal hearing, namely misunderstandings in the meaning of messages and delays in feedback from parents with hearing impairments. And there are efforts made to overcome obstacles when communicating, namely each individual family member will help each other provide understanding to anyone who does not understand the message they receive. So that it will give rise to good feedback